Ground Water Potential Zoning using GIS and AHP: Case Study of Bagmati River Basin, Nepal - Shahi, Kamal (Journal of Land Management and Geomatics Education, 2025)
Groundwater supplies around the world are under tremendous pressure due to overuse and noticeable climatic changes over time. The requirements to assess groundwater potential and aquifer productivity rise along with the global need for potable water for human consumption, agriculture, industrial applications and to maintain the ecological balance. GIS based techniques are being widely used to determine the potential zones for groundwater as it provides quick and first-hand information for further decision making. In this study, factors affecting the potential of groundwater availability such as material factors like geology, near surface and sub-surface soil features, structure, and drainage patterns and replenishment factors like rainfall, land use type, slope and lineament density were used in the GIS platform to perform the Multi Criteria Decision Analysis (MCDA) and weight allocation for each thematic layer was determined by AHP method. Bagmati river basin of Nepal having the area of 4337 sq.km was delineated in five categories namely Very Low, Low, Moderate, High and Very High as the potential of ground water availability. The result showed that 1 % of study area falls in the Very Low zone, 25 % in the Low zone, 45 % in the Moderate zone, 17 % in the High and 12% in the Very High zone of ground water potential. Also ground water potential zones were cross validated with reference to the available groundwater sources in the study region. Most of the available ground water sources lie in the high and very high zone of ground water potential within the basin.